(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2026)
The study entitled "Iraqi–American Relations Since 2021 and Their Future Prospects" examines the changes that occurred following the announcement of the withdrawal of U.S. combat forces and the transformation of their role into training, advisory, and technical support missions. It focuses on the nature of these relations in the current phase and the internal and external factors that continue to influence them — most notably Iranian influence and domestic divisions within Iraq. The study also discusses possible future scenarios of this relationship, with a stronger likelihood of continued relations, rather than drastic regression or a full strategic partnership. The significance of this research lies in its treatment of a contemporary topic that coincides with ongoing developments related to the strategic dialogue, the repositioning of U.S. forces, and shifts in Iraq’s foreign policy. The research adopts the descriptive-analytical approach, supported by case-study methodology, systems analysis, and political foresight. The study concludes that the relationship between the two sides remains structurally imbalanced; however, Iraq still significantly depends on U.S. support in the fields of security, counterterrorism, the economy, and energy — which reinforces the likelihood of continuity, albeit conditionally, depending on regional factors, especially the role of Iran. Keywords: Strategic Dialogue – United States of America – Iraq – U.S. Policy – Iran.